DIGITAL CONTACT POTENTIAL DIFFERENCE PROBE - K. U. Pantsialeyeu; A. I. Svistun; A. K. Tyavlovsky; A. L. Zharin (Приборы и методы измерений)
Nowadays the technique of analog contact potential difference probes well developed. Due to the influence of various parasitic factors, analog probes has substantial errors. The integration time for automatic CPD compensation should be at least several seconds to achieve high accuracy measurements. The speed and the accuracy are essential, for example, for Scanning Kelvin Probes. The purpose of this paper is to develop a digital contact potential difference probe, with a higher accuracy and speed of measurements as compared to analog probe. The digital probe made on base of 32-bit microprocessor with a Cortex M4 core. Measuring cycle consists of at least two successive determinations of the output signal amplitude at different compensation voltage generated by the microcontroller. It allows synchronizing of the generated oscillations and reading of the measuring signals. Data arrays processed in real time of the Digital Signal Processing by microprocessor. In this case is possible computation of the root mean square value or determination of the desired spectral line of the signal after fast Fourier transformation. Both methods permit eliminate of random noise and spurious harmonics. The method provides the digital contact potential difference probe operation in large signal mode and with a large signal/noise ratio. This eliminates the error associated with the zero signal finding. Also the integration time for automatic CPD compensation of the measured value is not necessary, which significantly reduces the measurement time and eliminates errors of compensation and DAC. In addition, the microcontroller could control the movement of the probe during scanning and transfer data to the host computer on interface USB, etc.